Surgical crown lengthening: a 12-month study - radiographic results - Daniela Eleutério Diniz; Kalizia Marcela Okuda; Clarissa Ribeiro Fonseca; Marly Kimie Sonohara Gonzalez; Sebastião Luiz Aguiar Greghi; Accácio Lins do Valle; José Roberto Pereira Lauris (University of São Paulo, 2007)
OBJECTIVE: The purpose of this study was to perform a radiographic follow-up evaluation after a 12-month healing period, following crown lengthening surgery. MATERIAL AND METHODS: Twenty-three periodontally healthy subjects (mean age 32.5 years) that required crown lengthening surgery in premolars were recruited. In a total of 30 premolars, full thickness flaps, osseous resection, and flap suturing were performed. The restorative margin was defined in the pre-surgical phase and maintained unaltered during the healing period, serving as a reference point. Standardized bitewing radiographs were taken before and after osseous reduction, and at 2, 3, 6, and 12-month healing periods. RESULTS: Intact lamina dura was observed at both mesial and distal alveolar crests only from the 3rd month. At 12-months, all alveolar crests presented lamina dura. The overall mean distance from the restorative margin to the alveolar crest achieved after osseous resection was 3.28±0.87 mm at mesial and 2.81±0.51 mm at distal sites. No significant radiographic changes in the bone crest were observed during a 12-month healing period. CONCLUSION: The findings of this study suggest that the radiographic proximal bone level observed on bitewing radiographs following crown lengthening surgery can be used as a reference to predict the future level of the healed alveolar crest.